(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is devoted to the development of linguistic culture in modern linguistics, arising as a result of the interdependence and influence of language and culture, the development of linguoculturology and the interpretation of language and culture in modern linguistics, at the same time the development of linguoculturology. The views of linguists who have made a number of successful attempts to explain the nature and existence of culturally significant features in the form of linguistic symbols from the perspective of linguistics, which focuses on cultural linguistics, have been studied in detail.